The Education and Training Role of Australian Academic Librarians. Issue 1 (2nd January 2019) - Manuell, Romany
ABSTRACT: Many academic librarians in university libraries perform a role in the education and training of university students, faculty staff and/or colleagues in areas related to information literacy. Anecdotal and empirical evidence suggests not all librarians are comfortable with this aspect of their position. How an individual conceives and understands their role may be influenced by complex historical, societal, national and personal contexts. The research student project summarised in this article will focus on an exploration of the relationships between education and training backgrounds and understanding and perceptions of the educative role by academic librarians in Victoria, Australia. The second aim of the study is to explore academic librarians' definitions and descriptions of their educative role. Using role theory as a framework to define the concept of role and phenomenography as an underpinning approach and research methodology, in-depth interviews with Australian academic librarians will be undertaken in 2019 in order to explore the connections between librarians' understanding of their educative role and their knowledge and practice of education and training.